1998
DOI: 10.1007/s003390051187
|View full text |Cite
|
Sign up to set email alerts
|

In situ scanning probe microscopy investigations of electroactive films

Abstract: Dimensional changes in electroactive films of nickel hydroxide, iridium oxide and polyaniline were investigated in situ in the electrochemical environment by scanning tunneling microscopy (STM), atomic force microscopy (AFM) and intermittent contact atomic force microscopy (ICAFM) during electrochemical oxidation and reduction. The advantages and disadvantages of the three measuring techniques are demonstrated with specific examples.While STM measurements are ambiguous due to the changing conductance of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
(17 reference statements)
2
8
0
Order By: Relevance
“…Increased PANI film thickness during oxidation was observed in these experiments also. This was also supported by a similar report from the same group few years later [25]. However, in this case the RMS roughness value was more at À0.2 V (2.7 nm) than that at +0.2 V (2.3 nm).…”
Section: Ec-afm Studies Of Pani Films In Chloride Mediumsupporting
confidence: 87%
See 2 more Smart Citations
“…Increased PANI film thickness during oxidation was observed in these experiments also. This was also supported by a similar report from the same group few years later [25]. However, in this case the RMS roughness value was more at À0.2 V (2.7 nm) than that at +0.2 V (2.3 nm).…”
Section: Ec-afm Studies Of Pani Films In Chloride Mediumsupporting
confidence: 87%
“…In this case 52% change in the volume of this island was observed from initial value. Swelling and shrinking of the PANI thin film (prepared electrochemically on HOPG) has been observed earlier during repetitive potential cycling in 1 M H 2 SO 4 [25]. From our measurements we could get quantitative details of volume changes with electrode potential in large single island of PANI-SO 2À 4 from the EC-AFM images obtained at constant potentials.…”
Section: Ec-afm Studies Of Pani In Sulphate Mediumsupporting
confidence: 66%
See 1 more Smart Citation
“…Häring et al reported the comparison of in situ imaging of PANI films during electrochemical doping-undoping processes using EC-STM, EC-AFM, and EC-intermittent contact-mode atomic force microscopy (IC-AFM) [141]. As Nyffenegger et al a few years earlier, they concluded that EC-STM is not well-adapted to the imaging of swelling/ deswelling of electronically conducting polymers, as the severe drop in the tunneling current expected to occur during the transition from the doped to the undoped state of the polymer will definitely lead either to artifacts or to damages to the polymer film during the imaging procedure.…”
Section: Ec-afm Investigations Of the Swelling/deswelling Of Ecpsmentioning
confidence: 99%
“…Siegenthaler and co-workers studied the in-situ AFM of PANI synthesized on HOPG with repetitive potential cycling in sulphate medium [9]. Recently, Szklarczyk and co-workers have done the in-situ AFM study of effect of monomer concentration on the morphology of poly (omethoxyaniline) [10].…”
Section: Introductionmentioning
confidence: 99%